2011
DOI: 10.1002/rcm.5209
|View full text |Cite
|
Sign up to set email alerts
|

Backtracking the movements of a migratory bird: a case study of a white‐fronted goose (Anser albifrons)

Abstract: The occurrence of avian influenza has brought attention to migrating birds and their migratory routes as possible carriers and gates, respectively, of the pathogenic influenza virus. There is a need to verify migration routes and to back-track the migration routes of infected animals. Stable isotope analysis of bird feathers is a valuable tool for studying the migratory pattern of birds, by gaining information about the environmental conditions during the growth of the feathers. Ideally, if different feathers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Horacek, 2011; Peterson and Williams, 2008; Whitworth et al, 2007), but there have been few attempts to evaluate the utility of this method. Yohannes, et al (2008) found that they could predict the prevalence of malaria in Great Reed Warblers ( Acrocephalus arundinaceus ) based on feather isotopes.…”
Section: Discussionmentioning
confidence: 99%
“…Horacek, 2011; Peterson and Williams, 2008; Whitworth et al, 2007), but there have been few attempts to evaluate the utility of this method. Yohannes, et al (2008) found that they could predict the prevalence of malaria in Great Reed Warblers ( Acrocephalus arundinaceus ) based on feather isotopes.…”
Section: Discussionmentioning
confidence: 99%
“…Combining isotopic signatures of feathers with knowledge of moult patterns has allowed the reconstruction of migration routes (Ramos et al 2009a), provided information on the possible transmission of the H5N1 strain of avian influenza (Chang et al 2008; Horacek 2011), and revealed variation in habitat preferences both within and between species during the nonbreeding period (Cherel et al 2006; Phillips et al 2009). This has enabled the migratory patterns and habitat selection of individuals during the winter to be linked to subsequent condition and breeding performance (Marra et al 1998; Furness et al 2006; Inger et al 2008) and identifies the geographical origins of pollutant burdens carried by seabirds (Leat et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…) and various mixtures of organic solvents, including acetone (Hilton et al . ; Horacek ), petroleum ether (Chang et al . ), chloroform‐ether 2 : 1 (Hobson & Wassenaar ; Cherel, Hobson & Weimerskirch ; Cherel et al .…”
Section: Introductionmentioning
confidence: 99%